Partitioning behaviours and selective recovery of therapeutic protein in aqueous two-phase system - Chow, Yin Hui (2016)
Immunoglobulin G (IgG) is a type of high value therapeutic protein widely applied to the treatment of various chronic diseases such as cancer, immune and inflammatory disorders. The conventional expensive and rate-limiting chromatography-based downstream processing of IgG has been considered as the bottleneck in producing commercially viable therapeutic products. This thesis focused on the development and application of aqueous two-phase system (ATPS) as an effective and economical approach to recover the IgG from crude feedstock. The partition of pure IgG and the extraction of IgG from an artificial mixture of proteins, which contained IgG and bovine serum albumin (BSA) at a concentration that simulates the common IgG/impurities ratio,were significantly affected by the polyethylene glycol (PEG) molecular weight, phase compositions, and the addition of sodium chloride (NaCl). The monoclonal human IgG1 was successfully recovered from the Chinese Hamster Ovary (CHO) cell supernatant by using an ATPS composed of 14.0% (w/w) PEG 1450, 12.5% (w/w) phosphate (pH 7.5),and 5.0% (w/w) NaCl in the first forward extraction. A total yield of 81.38%, high IgG purity of 95.06% and PF of 8.91 were achieved after the back extraction step. Also, relationship which describes the effect of the difference in composition of the phaseforming component between the top and bottom phases on the interfacial partitioning of protein as well as relationship which linearly correlates the protein partitioning behaviour to phase compositions and system pH were proposed and verified by studying the partitioning behaviour of a model protein, BSA, in the PEG-phosphate ATPS. The results of goodness of fit test showed that the former relationship and an extended form of the latter relationship, which incorporated with the influence of NaCl concentration, were both applicable to the correlation of the partitioning behaviour of IgG in the ATPS which contained complex protein solutions. The molecular dynamics (MD) simulation of the partitioning of BSA in an optimised ATPS confirmed that the ATPS is a biocompatible separation technique. Therefore, these results open a promising prospect for the application of ATPS as an effective alternative purification tool in the downstream processing of IgG.